The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5935/1678-9741.20140119
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of complex aneurysms and thoracic aortic dissections with the frozen elephant trunk technique

Abstract: ObjectiveReport initial experience with the Frozen Elephant Trunk technique.MethodsFrom July 2009 to October 2013, Frozen Elephant Trunk technique was performed in 21 patients (66% male, mean age 56 ±11 years). They had type A aortic dissection (acute 9.6%, chronic 57.3%), type B (14.3%, all chronic) and complex aneurysms (19%). It was 9.5% of reoperations and 38% of associated procedures (25.3% miocardial revascularization, 25.3% replacement of aortic valve and 49.4% aortic valved graft). Aortic remodeling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Dias et al, when publishing the initial experience of the group, emphasized that not only the severity of the underlying disease, the percentage of reoperations and the high number of associated procedures but also the learning curve could influence the results of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dias et al, when publishing the initial experience of the group, emphasized that not only the severity of the underlying disease, the percentage of reoperations and the high number of associated procedures but also the learning curve could influence the results of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results confirmed that the need for reintervention is due to the characteristics of the primary disease, and not because of the failure of FET's prosthesis. Besides, FET simplified reintervention in the distal segments, providing a more appropriate landing zone for endovascular completion …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With our in situ stent graft fenestration technique, anastomosis of the LSA was simplified, and the circulatory arrest time was shorter in our study than in the study by Dias et al (23.28 6 5.56 minutes vs 40 6 8 minutes). 15 In addition, the results of cerebral complication were encouraging as only five (4.7%) patients had transient neurologic dysfunction, and no permanent neurologic dysfunction occurred.…”
Section: Discussionmentioning
confidence: 85%
“…We have read the interesting article entitled "Surgical treatment of complex aneurysms and thoracic aortic dissections with the Frozen Elephant Trunk technique" carefully [ 1 ] . The authors report their initial experience with this technique in 21 patients.…”
mentioning
confidence: 99%